The blinded state - Panov, Mitko (Mitko B.), author.
1 online resource.
Keywords: This book is a revisionist account of Samuel's State and the legendary struggle between Samuel Cometopoulos and Basil II (10th-11th century). It goes beyond the standard approach to the study of state formation, presenting an entirely new analytical framework which interrogates how contemporaries in the Balkans at different times, ranging from the Byzantine and Balkan elites of the medieval centuries to later voices in the early modern and modern periods, have represented Samuel's polity in the service of their own political agendas and territorial aspirations towards Macedonia. The wide-ranging relationship between culture, identity and power are addressed, making use not just of Balkan literary and artistic traditions but on writings from across the Slavic world and western political and intellectual contexts. Demonstrating the conflicted legacy of the Samuel's State in the Balkans, Mitko B. Panov questions established scholarly opinion and offers new interpretations that reconsider its place in Byzantine and Balkan history and imagination.